Displacement detection in human vision - Legge, Gordon E.; Campbell, F.W. (Vision research (Oxford), 1981)
The displacement threshold is defined to be the smallest instantaneous target displacement that can be detected. Properties of the displacement threshold for a small, luminous spot were measured psychophysically. In a structureless field, the displacement threshold was near 1.5′, subject to individual variation. The effects of pattern were studied by measuring displacement thresholds at the centers of a set of annuli ranging from 2.85′–728′ dia. Displacement thresholds were reduced by the presence of the annuli and were as low as 0.3′. This threshold reduction could not be fully attributed to processes of relative spatial localization because displacement thresholds were lower than spatial localization (bull'seye) thresholds for annulus diameters greater than 20′. The displacement threshold is virtually independent of orientation and pupil size. It increased about 75% with a three log unit decrease in photopic target luminance. Displacement detection appears to depend upon the motion sense rather than the position sense. It may be limited by fixation accuracy.